Implementación de las buenas prácticas de manufactura en la microempresa “Encholados” Manta - Pazmiño Marcillo, Dariana Lisbeth (2026)
The objective of this research was to implement good manufacturing practices manuals to improve the quality of frozen yogurt at the microenterprise "Encholados" in Manta. A non-experimental, mixed-method approach was used, based on descriptive, field, and documentary methods. In the diagnostic phase, a verification guide based on ARCSA DE2022-016-AKRG regulation was applied, achieving overall compliance of 39.04% and noncompliance of 40.64%. After implementing the GMP manuals, the results showed an increase in the level of conformities to 74.33% and a reduction in nonconformities to 10.70%. In parallel, staff were interviewed and trained, strengthening their knowledge in hygiene, food handling, and quality control. The impact of the intervention was evaluated by using the T-Student test for related samples, comparing compliance levels before and after the implementation. In conclusion, the incorporation of GMP manuals, along with staff training, significantly improved regulatory compliance and increased product safety, with statistical confirmation of its positive effect.